Spectroscopy and dynamics of the bond, inter- and intra molecular! - Das, Arijit (2020)
In 2009, Goswami and Arunan proposed a condition for hydrogen bonding according to which there should at least be one bound-level along vibrational coordinates which lead to breaking of the hydrogen bond. They showed that this is the significant difference between the open tetrahedron structure of ice and the close packed structure of solid H2S, and they are not the results of the difference between ‘hydrogen bonding’ and ‘van der Waals interactions’ as commonly assumed. When it comes to the dimers of H2O and H2S, there were plenty of experimental and theoretical results available for the former and very little for the latter. Recently, our group in collaboration with Newcastle University, UK and the National Institute of Standards and Technology, U.S.A. have observed the K=1 transitions of H2S dimer which unambiguously showed that H2S dimer is hydrogen bonded. We have now calculated the barriers along the various large amplitude motions in H2S dimer and shown that it indeed satisfies the criterion of Goswami and Arunan.